Phrasal Verbs Translation in Lore Olympus Webtoon Digital Comic - Purba, Feby Febriyani; Yuliah, Siti; Rahmah, Ilma Yullinda; Arnoi, Khoirun Nisaa (Jurnal Bahasa Inggris Terapan, 2025)
This present study aims to observe: (1) the translation strategies used to translate phrasal verbs from English into the Indonesian language based on Baker’s theory; and (2) the translation assessment of phrasal verbs focusing on the accuracy and acceptability aspect based on Nababan’s parameter. This study is classified as a descriptive qualitative because the data consists of a lingual unit, specifically phrasal verbs. The analysis is also supported by simple calculations to determine the frequency and percentage of each translation strategy and its accuracy and acceptability. The data source is a Line Webtoon digital comic entitled Lore Olympus which analyzes the English and Indonesian phrasal verbs translation. The results show as follows: (1) there are only three translation strategies used, namely paraphrasing (95%), omitting the entire idiom (3.3%), and omitting a play on idiom (1.7%). (2) The translation of phrasal verbs is mostly considered accurate (93.3%) and fully acceptable (100%). Based on the findings, it implies that the translator of a digital comic Lore Olympus should prioritize paraphrasing strategies to maintain accuracy and acceptability when translating phrasal verbs from English into Indonesian.